2017
DOI: 10.4049/jimmunol.1601588
|View full text |Cite
|
Sign up to set email alerts
|

Inducible TAP1 Negatively Regulates the Antiviral Innate Immune Response by Targeting the TAK1 Complex

Abstract: The innate immune response is critical for host defense and must be tightly controlled, but the molecular mechanisms responsible for its negative regulation are not yet completely understood. In this study, we report that transporter 1, ATP-binding cassette, subfamily B (TAP1), a virus-inducible endoplasmic reticulum-associated protein, negatively regulated the virus-triggered immune response. In this study, we observed upregulated expression of TAP1 following virus infection in human lung epithelial cells (A5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…A549 IFNAR1 KO cell line was generated by CRISPR-Cas9 system described before[37]. The following oligonucleotides specific targeting the IFNAR1 gene were used:…”
Section: Methodsmentioning
confidence: 99%
“…A549 IFNAR1 KO cell line was generated by CRISPR-Cas9 system described before[37]. The following oligonucleotides specific targeting the IFNAR1 gene were used:…”
Section: Methodsmentioning
confidence: 99%
“…LYAR-overexpressed or LYAR-KO HEK293T cells were infected with VSV-GFP or Sev at an MOI of 1.0. Viral supernatants were harvested at the indicated time points postinfection, and plaque assays were performed on Vero cells to titrate the VSV titer as described previously (50). To detect the Sev virus titer, Vero cells were seeded in 96-well plates before Sev virus infection.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this, Huang et al reported the transcription factor peroxisome proliferator-activated receptor gamma (PPAR-γ) as a negative regulator of inflammation during IAV infection in alveolar macrophages (AM) as PPAR-γ deficiency in AM enhanced pulmonary inflammation and host morbidity [ 216 ]. Similarly, transporter 1, ATP-binding cassette, subfamily B (TAP1) is shown to be upregulated upon IAV infection and inhibit NF-κB-mediated proinflammatory cytokine production by targeting the TAK1 complex [ 217 ]. Furthermore, the NLR family protein NLRX1 is also reported to attenuate IAV induced inflammation by meddling with the RIG-I-MAVS signaling pathway and TRAF6 ubiquitin ligase, an essential component of antiviral TLR signaling [ 218 ].…”
Section: Negative Host Regulatorsmentioning
confidence: 99%